RETRACTED: Development of quality control methods for measurements and testing concrete structures - Belentsov Yuriy; Rybalko Alisa (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001